Innovation in the Public Sector - United Nations Economic Commission for Europe (United Nations, 2021)
The public sector plays a very significant role in modern economies. As in the business sector, innovation can be a major source of productivity growth, cost savings and improvements in service quality in the public sector, benefits which then also positively affect businesses and citizens who rely on an efficient and effective public sector. The ability of the public sector to innovate is therefore increasingly seen as a critical element of economy-wide innovation performance. This publication covers a wide range of issues related to the promotion of innovation in the public sectors as well as policy lessons learned in this area drawing on the experiences of different countries.